2021
DOI: 10.1080/23279095.2021.2003365
|View full text |Cite
|
Sign up to set email alerts
|

Digital neuropsychological test performance in a large sample of uninjured collegiate athletes

Abstract: Digital neuropsychological test batteries are popular in college athletics; however, well-validated digital tests that are short and portable are needed to expand the feasibility of performing cognitive testing quickly, reliably, and outside standard clinical settings. This study assessed performance on digital versions of Trail Making Test (dTMT) and a modified Symbol Digit Modalities Test (dSDMT) in uninjured collegiate athletes (n ¼ 537; 47% female) using the C3Logix baseline assessment module. Time to comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…However, with the development of artificial intelligence technology, many shortcomings of traditional cognition assessments can be overcome [ 13 , 15 ]. Several studies have found that a comprehensive assessment of cognition can reflect a patient’s real status [ 16 ]. Although many studies have focused on developing models based on the Clock Drawing Test [ 17 , 18 ] and Rey Complex Figure Test [ 19 , 20 ], there is a relative scarcity of studies based on the TMT.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the development of artificial intelligence technology, many shortcomings of traditional cognition assessments can be overcome [ 13 , 15 ]. Several studies have found that a comprehensive assessment of cognition can reflect a patient’s real status [ 16 ]. Although many studies have focused on developing models based on the Clock Drawing Test [ 17 , 18 ] and Rey Complex Figure Test [ 19 , 20 ], there is a relative scarcity of studies based on the TMT.…”
Section: Introductionmentioning
confidence: 99%